2010
DOI: 10.1053/j.gastro.2010.01.032
|View full text |Cite
|
Sign up to set email alerts
|

HuR/Methyl-HuR and AUF1 Regulate the MAT Expressed During Liver Proliferation, Differentiation, and Carcinogenesis

Abstract: Background & Aims-Hepatic de-differentiation, liver development, and malignant transformation are processes in which the levels of hepatic S-adenosylmethionine (SAMe) are tightly regulated by two genes, MAT1A and MAT2A. MAT1A is expressed in the adult liver, whereas MAT2A expression is primarily extra-hepatic and is strongly associated with liver proliferation. The mechanisms that regulate these expression patterns are not completely understood. In silico analysis of the 3′ untranslated region of MAT1A and MAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
146
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 115 publications
(155 citation statements)
references
References 35 publications
9
146
0
Order By: Relevance
“…HCC specimens express higher AUF1 protein levels, and knockdown of AUF1 increased MAT1A mRNA level (23). However, these mechanisms are difficult to target, since they can affect numerous other genes.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…HCC specimens express higher AUF1 protein levels, and knockdown of AUF1 increased MAT1A mRNA level (23). However, these mechanisms are difficult to target, since they can affect numerous other genes.…”
Section: Figurementioning
confidence: 99%
“…showed that the MAT1A 3′ UTR binds to the AU-rich RNA binding factor 1 (AUF1), which is one of the hnRNP proteins known to destabilize target mRNAs (23). HCC specimens express higher AUF1 protein levels, and knockdown of AUF1 increased MAT1A mRNA level (23).…”
Section: Figurementioning
confidence: 99%
“…15). Slides were then incubated with primary anti-HuR antibody (EMD Millipore) followed by biotinylated secondary antibody.…”
Section: Ihcmentioning
confidence: 99%
“…HuR can exist in methylated or un-methylated form. While, the presence of methylated HuR protein is associated with destabilization of MAT2A mRNA and decreased expression of α2 subunit of MAT II isoform, the un-methylated HuR exerts an opposite effect (Vázquez-Chantada et al 2010).…”
Section: Effect Of Altered Expression Of Mat Genes On Carcinogenesismentioning
confidence: 99%